Práticas de leitura no ensino de língua portuguesa: possibilidades de aprendizagens no 9o ano da Escola Municipal Dom Ricardo Pedro Paglia, município de Presidente Sarney – MA - PEREIRA, Emídia Ferreira Alves (2023)
In this research it is questioned to what extent the reading practices developed in the teaching of Portuguese in the 9th grade at Dom Ricardo Pedro Paglia Municipal School (municipality of Presidente Sarney) have contributed to the process of training readers and to the development of other apprenticeships. The objective is to analyze these practices according to the concepts in use by the teachers of this subject and their contributions to the formation of readers, aiming at the elaboration of a Pedagogical Notebook as a methodological proposal in an interactional discursive perspective of the language that re-signifies them. Bibliographical and documental research and action-research (collaborative type) are used, guided by the Historical- Cultural approach: in the first one, we reference studies and theorists that approach reading in the dialogic-discursive perspective and their respective practices; in the second one, through normative documents of basic education, such as the BNCC (Base Nacional Comum Curricular in Portuguese, or Brazilian National Common Core Curriculum) and the DCTMA (Documento Curricular do Território Maranhense in Portuguese, or Commom Core Curriculum from Maranhão State) that establish the core curriculum guidelines at the national and state levels; in the third one, supported by Participant Observation, the Pilot Diagnosis/Diagnosis and the Interview as instruments for data generation. It is identified in the investigation, the lack of reading practices that guarantee the necessary interaction between text/discourse and involved readers, and of strategies that favor the teacher's mediation and the understanding of what is read in the teaching of Portuguese; on the other hand, the prevalence of the conception of reading as a decoding or assimilation process, with the text as an object to be decoded and reproduced, according to the proposals suggested for evaluation purposes. A contribution is made here to the respective epistemological field, as well as to the pedagogical praxis referring to the reading practices promoted by the Portuguese Language teachers of the aforementioned institution, with the elaboration of a Pedagogical Notebook of Reading Practices in a collaborative way based on the results, which is organized around four didactic sequences anchored in the discursive interactional perspective of language/reading, in order to reconfigure and reframe reading practices mediated in the school context.